Brazilian Youth and Science: Possible Relationship of Interest (Revista Brasileira de Pesquisa em Educação em Ciências, 2016)
The decline in interest of young people in a science career, observed in several countries, has led to a movement in favour of listening to students’ opinions about their science classes, science and science careers. One of these movements is the project “The Relevance of Science Education” (ROSE), implemented in over 40 countries and the subject matter of the work described in this paper. In this sense, this article aims to verify the overall interest of young people in school science, a science career and a job that deals with advanced technology. The Brazilian sample, taken in 2010, is representativeon a nationwide basis, involving 2,365 students from 84 Brazilian schools. The data revealed that young Brazilians are interested in school science, but have little interest in pursuing a science career. There is interest however, in relation to jobs that deal with advanced technology, especially among boys. The international survey had showed negative relationship between the HDI of the countries surveyed and students’ interest in science: the higher the HDI, the lower the interest. The results indicate the need to reflect on the possible actions that can be taken in order to narrow the gap between the interest in school science and science career, and to understand the reasons for theexistence of this gap.